A comparison of heart rate response and frequencies of technical actions between half-court and full-court 3-a-side games in high school female basketball players - Atl, H.; Köklü, Y.; Alemdaroglu, U.; Kocak, F. Ü. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to compare heart rate (HR) response and frequency of technical actions between half-court and full-court 3-a-side games in female high school basketball players. Twelve young female basketball players (age 15.5 ± 0.5 years; height 165.1 ± 5.7 cm; body mass 57.3 ± 7.2 kg; training age 4.2 ± 0.7 years; HRmax 202.9 ± 5.6 b/min) participated in this study voluntarily. On the first day, anthropometric measurements (height and body mass) were taken for each player; this was followed by the Yo-Yo intermittent recovery test (YIRT) level 1 for the subjects. Then, half-court and full-court 3-a-side games were organized in random order at 2-day intervals. The HRmax for each player was determined during the YIRT, after which the HR was measured during the 3-a-side games. In addition, the frequencies of different categories of technical actions were counted manually during the 3-a-side games. A paired t-test was calculated for each dependent variable, including HR, percentage of maximum HR (%HRmax), and the frequencies of different technical actions to compare half-court and full-court 3-a-side games. The study results indicate that the full-court 3-a-side games produced significantly higher responses than the half-court 3-a-side games in terms of HR and %HRmax (p < 0.05), whereas the half-court games resulted in significantly higher frequencies of technical actions (p < 0.05). The results of this study suggest that, if coaches want to achieve greater HR responses, coaches of female high school basketball players should organize full-court 3-a-side games, whereas coaches who want to focus on technical actions should arrange half-court 3-a-side games.